Urgensi Literasi Digital di Indonesia pada Masa Pandemi COVID-19: Sebuah Tinjauan Sistematis - Iqbal Faza Ahmad (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Digital literacy competence is very important for students, especially during the COVID-19 pandemic. The application of distance learning encourages easy internet access for every level of society. This paper intends to conduct a study of digital literacy in Indonesia during the COVID-19 pandemic. The research method in this research is a systematic review. The research findings show that digital literacy campaigns are important during the COVID-19 pandemic. Digital literacy will foster a creative and critical mentality in dealing with the COVID-19 outbreak. The digital literacy movement will help the public obtain the right information and pass the time during the COVID-19 outbreak. In addition, there are important components in developing digital literacy, namely as follows. 1) Culture, namely understanding the various contexts of users of the digital world; 2) Cognitive, namely the power of thought in assessing the content; 3) Constructive; 4) Communication, namely understanding network and communication performance in the digital world; 5) Confident in being responsible; 6) Creative, doing new things in new ways; 7) Critical in addressing content; 8) Being socially responsible.